Pure Coulomb tensor interaction in the Dirac equation - Garcia, M. G.; Pratapsi, S.; Alberto, P.; Castro, A. S. de [UNESP] (Amer Physical Soc, 2019)
In this work we compute bound solutions for particles and antiparticles of the Dirac equation for a pure tensor radial Coulomb potential plus a constant. We find that the binding depends on the sign of the tensor constant potential, and allows only bound solutions for a certain sign and magnitude of the kappa quantum number, which is related to the spin-orbit coupling in the Dirac equation. This relation is reversed for antiparticle solutions. On the other hand, the Coulomb tensor potential, although not binding, changes the range of kappa values for which there are bound solutions.